1966
DOI: 10.1152/ajplegacy.1966.211.6.1299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium on membrane potential, spike discharge, and tension in taenia coli

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1966
1966
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…It was also reported that an acid extracellular pH decreased the glucose uptake in the rat heart (14). These findings cited above might explain some possible mechanism of the inhibition by low external pH or low concentration of sodium bicarbonate in the medium on the K-contracture, the phasic phase of which was said to be initiated by the released of tissue calcium (3)(4)(5) and the tonic phase diminished when external glucose was removed from the external medium (3), but no experimental evidence has been ob tained in the case of taenia coli. Total calcium content of taenia coli kept in the phosphate-free Krebs-Ringer (2.8 mm Ca/kg fresh wt.)…”
Section: Sodium Phosphatementioning
confidence: 76%
See 1 more Smart Citation
“…It was also reported that an acid extracellular pH decreased the glucose uptake in the rat heart (14). These findings cited above might explain some possible mechanism of the inhibition by low external pH or low concentration of sodium bicarbonate in the medium on the K-contracture, the phasic phase of which was said to be initiated by the released of tissue calcium (3)(4)(5) and the tonic phase diminished when external glucose was removed from the external medium (3), but no experimental evidence has been ob tained in the case of taenia coli. Total calcium content of taenia coli kept in the phosphate-free Krebs-Ringer (2.8 mm Ca/kg fresh wt.)…”
Section: Sodium Phosphatementioning
confidence: 76%
“…Phasic contraction was said to be initiated by the passive process of release of calcium from a cellular site whereas tonic contracture by the active transmembrane calcium transport linked to metabolism (3)(4)(5). If the process(es) common to both phases should exist, it (they) may be before and/or after than the aformentioned processes.…”
Section: Sodium Phosphatementioning
confidence: 99%
“…Only an initial transient contraction is induced by high K (and also by carbachol) in the presence of Ca antagonists like verapamil (Riemer et al, 1974;Karaki et al, 1984), D600 (Brading & Sneddon, 1980), ruthenium red (Kawamura & Yabu, 1978), cyproheptadine (Lowe et al, 1981) and N2-dansyl-L-arginine-4-t-butylpiperidine amide (TI 233) (Karaki et al, 1983c), inhibitors of aerobic metabolism (Pfaffman et al, 1965;Ferrari & Carpenedo, 1968 ;Tsuda et al, 1977;Nakagawa et al, 1984), inhibitors of the Na pump like ouabain (Pfaffman et al, 1965;Kishimoto & Urakawa, 1982a), Li substitution for Na (Pfaffman et al, 1965;Kishimoto & Urakawa, 1982a), and ionophores with mitochondrial inhibiting action like monensin and X-537A (Ishida & Shibata, 1982;Murakami et al, 1983). The initial transient contraction induced by high K in taenia coli coinsides with a burst of spike discharges (Shimo & Holland, 1966). This electrical change, as well as initial transient contraction, is relatively insensitive to the inhibitory effects of Mn (Brading et al, 1969) and D600 (Inomata & Kao, 1976).…”
Section: Initial Transient and Following Sustained Contractionsmentioning
confidence: 99%
“…In rabbit aorta, an increase in external K concentration induces only a graded depolarization (Mekata, 1976). In taenia coli, as well as in other spike-generating smooth muscles like uterus, vas deferens and ureter, an increase in the external K concentration induces a burst of spike discharges followed by a spike-free membrane depolarization (Burnstock et al, 1963;Shimo & Holland, 1966 ;Bolton, 1972;Johnishi & Sunano, 1978). In guinea pig portal vein, a hyperosmotic solution itself depolarizes the membrane (Kuriyama et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The tonic contraction results from a steady depolarization, and the coupling between the depolarization and the contractile system is Ca and metabolism-dependent (14,15). Clonidine was scarcely effective in altering the 80 mM potassium-induced response at a 0.3 mM level.…”
Section: Effects Of Clonidine On 80 Nial Potassium-in(hiced Responsementioning
confidence: 99%